OBESITY: A CAUSATIVE RISK FACTOR OF BREAST CANCER - A. S. Roy; S. Basu; A. Bandyopadhyay (International Journal of Medicine and Medical Research, 2019)
Background. Obesity, a global health burden and one of the most deleterious diseases have substantially increased prevalence attributable to changing lifestyle of modern times. Persuasive evidence indicates obesity as an independent prognostic factor for developing malignancy in the form of breast cancer particularly in post-menopausal women.